THE RELATIONSHIP OF DIET WITH OBESITY IN ELEMENTARY SCHOOL CHILDREN - Noviyanti, Noviyanti; Ulandari, Yolanda; Indriyani, Indriyani; Oktariza, Rury Tiara; Anggaraini, Wieke (Syifa'Medika, 2024)
Obesity has become a worldwide epidemic health problem. The World Health Organization says that more than 1.9 billion adults aged 18 years and under are overweight and 600 million of them are obese. Obesity in children is a risk factor for various diseases such as cardiovascular and metabolic disorders. A sedentary lifestyle/excess can be a factor in the occurrence of obesity, one of which is a bad diet. The purpose of this study was to determine the relationship between diet and obesity in elementary school children. This type of research is quantitative-analytical, observational, and cross-sectional as the research design. The sampling technique uses total sampling conducted on Class V children of State Elementary School 104 Palembang. The obesity variable is measured using a z score, while diet is measured using the Food Frequency Questionnaire (FFQ). The data was processed and analyzed using the chi-square test. The results of this study were from 86 respondents obtained more children who were not obese than children who were obese, namely 15 respondents with a percentage (17.4%) who were obese and as many as 71 respondents with a percentage (82.6%) who were not obese. The results of the chi-square test obtained a p-value of 0.045. The conclusion is that there is a relationship between diet and obesity in elementary school children of Negeri 104 Palembang.